PENGARUH OVERHEATING TERHADAP TERJADINYA DISTORSI DAN HASIL RT PADA PENGELASAN GTAW UNTUK MATERIAL SOLID INCONEL UNS N06625 - Aran, Mikhael Milang; Susilo, Trisno; Hilmy, Zakwan (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2024)
WPS has several parameters that determine heat input. This research was conducted to determine the welding results when the heat input used exceeds the value specified in the WPS used in the field. The research was carried out on 3 samples that have the same dimensions, namely 2" diameter with a thickness of 5.54 mm. The research method used was quantitative experimental. The weld results are checked visuallythen continued with the NDT process in the form of RT. At each increase in heat input, there is a distortion of 4 mm and 1 number of RT weld defects in the heat input more than 10% WPS, distortion of 6 mm and 2 number of weld defects in the heat input more than 20% WPS, distortion 8 mm and 3 number of weld defects in the heat input more than 30 % WPS. The T test results show that overheating influences the occurance of distortion and RT results in GTAW welding. From the research results, it can be concluded that the higher the heat input used in the GTAW welding process for Inconel UNS N06625 material, the higher the distortion and number of weld defects in the welding results.